PEMBELAJARAN PARTISIPATIF BERMEDIA BAAMBOOZLE PADA MATA PELAJARAN FIKIH DI MA WAHID HASYIM BALUNG - Aj’matul Laili; Dhevin MQ Agus Puspita W (Fakultas Tarbiyah, Universitas Ibrahimy, 2025)
Among the problems of learning Islamic religious material is the low pedagogic competence of teachers, both related to learning planning and implementation. This problem is complained about in several schools, both public and private schools. In fact, in one school between subject teachers, there was an inequality of pedagogic competence. At MA Wahid Hasyim, there are Fiqh teachers who have pedagogic competence that exceeds that of other teachers. This is reflected in Fiqh learning which is attended by students who are very participatory with the application of Baamboozle media. This interest needs to be revealed through qualitative research by collecting data on interviews, observations, and documentation of Fiqh learning activities with Baamboozle media. There are three conclusions resulting from this study, namely: (1) The Learning Process which includes planning, implementation, and evaluation of the process can run well in the hands of innovative Fiqh teachers; (2) The impact of Baamboozle-mediated Fiqh learning can create active, interactive, participatory, competitive, and fun learning; and (3) Supporting factors for Fiqh learning with Baamboozle media can be carried out, namely adequate pedagogic competence of teachers, sufficient relevant facilities, and student enthusiasm.